2019
DOI: 10.1108/ijcthr-07-2018-0092
|View full text |Cite
|
Sign up to set email alerts
|

Street foods: contemporary preference of tourists and its role as a destination attraction in India

Abstract: Purpose The study aims to assess and find out the preference of street-foods amongst the foreign tourists visiting India. It will also discuss in detail the important factors that lead to the selection of street-foods outlining the relevance of food as a destination attraction. Design/methodology/approach The study applied the use of location intercept technique through one to one interview using a structured survey scale to take the responses from 586 outbound foreign tourists at the departure gates of Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Guiding impacts on overall tourist satisfaction (Huang et al , 2010). Local guides' attributes, perceived food authenticity, local culture and novelty components agree with previous studies' findings (Gupta et al , 2018, 2019; Jeaheng and Han, 2020; Seyitoğlu, 2020a, b; Sthapit, 2017). However, ‘perceived hygiene or cleanliness' components are not explored in prior studies because this was provided with the help of local guides, and participants trust them due to that they know these street foods.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Guiding impacts on overall tourist satisfaction (Huang et al , 2010). Local guides' attributes, perceived food authenticity, local culture and novelty components agree with previous studies' findings (Gupta et al , 2018, 2019; Jeaheng and Han, 2020; Seyitoğlu, 2020a, b; Sthapit, 2017). However, ‘perceived hygiene or cleanliness' components are not explored in prior studies because this was provided with the help of local guides, and participants trust them due to that they know these street foods.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Present studies (e.g. Gupta and Sajnani, 2019; Gupta et al , 2019) suggest that tourists are motivated to try the cultural tastes of a destination and are inspired to engage real-life ways of the locals to acquire the authentic tourist experience. Their cultural and culinary experiences are impacted by their level of questing for authenticity (Ji et al , 2016).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reveals the effect of street food experience on behavioural intention and shows its importance to destination management organisations or local governments. Gupta et al (2020a, b) suggested that street food vendors can be thought of as a strategic management tool that can (re)create a destination image and sustain or stimulate tourist movements towards the destination. Besides, they suggested that street food vendors in India could help develop strategies to present India on a global gastronomic platform (Gupta et al , 2020b, p. 136).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Gupta et al (2020a, b) suggested that street food vendors can be thought of as a strategic management tool that can (re)create a destination image and sustain or stimulate tourist movements towards the destination. Besides, they suggested that street food vendors in India could help develop strategies to present India on a global gastronomic platform (Gupta et al , 2020b, p. 136). In another study conducted in India, Gupta and colleagues investigated how the overall destination experience of foreign tourists to India is influenced by the existing variety of street food in India, and how these traits further affect tourist behaviour intentions (revisit intention and word of mouth).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%